Resolve partially the inner disk for Epsilon Eridani. Issue 1 (March 2021) - Taha, Anas S.; Rashed, Y. E.; Kadhem, Arshed A.
Abstract: We present mid-infrared imaging observations of the debris disk around one of the main sequence star Epsilon Eridani in the Q-band at (20.5 µm) and (17.6 µm). The dust that produces emission in debris disk is spatially resolved in the inner region of the debris disk of Epsilon Eridani at distance approximately between 1.4 - 4 AU. Method: The target has been observed Epsilon Eridani using the GTC (Gran Telescope Canaria) with CanariaCam instrument, which performs imaging in mid-IR (Q-band). To detect the disk around Epsilon Eridani star, we observed a standard star and the target star, consequently. We then measured the PSF (Point Spread Function) of our standard star to limit the radial flux profile of our target star. The images were centred to the center images before subtracted the radial flux of the standard star from the radial profile of science target to get the residual flux which is produced by the debris disk. The first important step is removing the background effect from images with contribution flux of star. For this, we calculated the standard deviation of background as well as the seeing variation during the observation to estimate the value of stellar flux residuals. Result: The dust emission around the debris disk is spatially resolved and the size of the emission is determined. The dust detected around Epsilon Eridani is located in the same distance from the star where a giant planet has confirmed. The photometry measurements are achieved for emission 0.268 Jy and the flux of the star is 2.18 Jy.